Unnecessary shock from an implantable cardioverter-defibrillator following transcutaneous pacing. Issue 4 (July 2014) - Somani, Riyaz; DeJong, Peggy; Michael, Kevin; Baranchuk, Adrian
ABSTRACT: As the population ages and cardiovascular disease becomes more prevalent, an increasing number of patients are receiving implantable cardioverter-defibrillators (ICDs). When these patients present to the emergency department, it is imperative that physicians are not only aware of the possible underlying medical issues that may have precipitated their admission but should also have a good understanding of the potential interactions that any medical intervention may have on the patient's device. We discuss a case in which a patient known to have an ICD in situ was transcutaneously paced for the management of bradycardia, leading to an unnecessary shock.